Wide-range displacement sensor based on variable line-spacing grating and Y-type twin-core fibre. Issue 21 (14th December 2020) - Zhao, Jiaqi; He, Wei; Meng, Fanyong; Chen, Guanghui; Dong, Mingli
Abstract : In the paper, a wide range displacement sensor based on the variable line-spacing (VLS) grating was proposed and its displacement characteristics at different temperature environments were measured. The VLS grating was inscribed by electron beam lithography method, and the sensor mechanical structure was designed and fabricated. A broadband light was irradiated to the VLS grating though a twin-core Y-type fibre, and an aluminizing reflector mirror was used to adjust light spot positions to change the displacement. In the experiment, the temperature stabilities of sensor were tested when the temperature rose from −20°C to 60°C, and the maximum drift of diffraction peak was less than 1.01 nm. In 30 mm length displacements, the diffraction wavelength was shifted simultaneously, the sensitivity was 15.941 and 15.917 nm/mm at 20°C and 50°C respectively, and the linearity was 0.994 both at 20°C and 50°C.